THE EFFECT OF COMPETENCY DEVELOPMENT AND EMPOWERING LEADERSHIP ON SUBJECTIVE CAREER SUCCESS WITH SELF-EFFICACY AS A MEDIATING VARIABLE IN EMPLOYEES OF THE WEST SUMATRA EMPLOYMENT SOCIAL SECURITY AGENCY - Sukma Mayliza; Rino Rino (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effect of competency development and empowering leadership on subjective career success with self-efficacy as a mediating variable among employees of the West Sumatra Employment Social Security Agency (BPJS Ketenagakerjaan). The research method used is descriptive quantitative, with a sample of 117 patients. The analysis used is PLS-SEM analysis with Smart-PLS 4.0. The results of the study show that there is a positive and significant effect between Competency Development and Empowering Leadership on Subjective Career Success with Self-Efficacy as a Mediating Variable in Employees of BPJS Ketenagakerjaan West Sumatra, meaning that leaders who provide empowerment (delegation, trust, and autonomy) are proven to encourage employees to feel more successful in their subjective careers. The mediating role of self-efficacy can enhance Competency Development and empowering leadership styles not only directly influence but also increase employees' self-efficacy. This high level of self-confidence (mediation) acts as a bridge that strengthens the impact of Competency Development and empowering leadership on subjective career success.